ISLAMIC FAMILY LAW ON POLYGAMOUS MARRIAGE IN MALAYSIA: BETWEEN ROSES AND THORNS (Jurnal Pembangunan Sosial, 2024)
Marriage is a way of gaining a peaceful mind and soul, be it monogamous or polygamous marriage. This is the sweetness of marriage as enshrined by Islam. To achieve this wisdom, conditions laid down by the religion and legal requirements must be observed. Otherwise, a marriage may turn into a miserable and thorny life for couples, especially in polygamy. Thus, the purpose of this paper is to disseminate legal knowledge and refine the understanding about polygamous law in Malaysia. The central arguments of this study are two-pronged: (1) to deliberate on the Malaysian legal framework for polygamous marriage and (2) to discuss a crucial legal issue related to polygamy, namely cross-border marriage and its effects. The qualitative method of doctrinal legal research was employed to obtain and analyse primary and secondary data from various sources. It included examining the statutes and decided cases of the Syariah Courts, including reported and unreported cases. The relevant statutes studied were the Islamic Family Law (Federal Territories) Act 1984 and the Enactment of Islamic Family Law (Kedah Darul Aman) 2008. In substantiating arguments, data from e-Syariah Version 3 (ESV3) was used together with existing literature. The findings revealed that refusal or failure to comply with legal requirements pertaining to polygamous marriage may lead to cross-border marriage and its aftermath effects on the legality of the marriage, jurisdiction of the court, and the rights of wives and children in the context of law. Hence, the enforcement of existing laws on polygamy should be emphasised to control any abuse of power by a man to contract a polygamous marriage. More importantly, the laws and enforcement should be strengthened to protect the rights of the wives and children. Future research may focus on issues involving the rights of the wives and children of a polygamous marriage upon the death of the husband or father according to Islamic family law in Malaysia and its implementation.